The modern state and prospects of the development of Ukrainian passenger river fleet - Borysenko, Petro (Skhid, 2013)
The main social and economical problems of the Ukrainian passenger river fleet are analyzed in the article; his potential and prospects of the development in modern conditions are defined. Considerable attention is spared to the problems of river fleet's, infrastructure and also its role for civil shipbuilding.